NUTRITION STATUS AND ACADEMIC ACHIEVEMENT OF LEARNING FOR ELEMENTARY SCHOOL CHILDREN 6 SANUR - Ida Ayu Purnama Dewi; I Komang Agusjaya Mataram; Hertog Nursanyoto (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2021)
Nutrition is one of the main determinants of the quality of Human Resources. Good nutritional status will affect the process of growth and development of children, one of which can improve intellectual abilities that will have an impact on learning achievement in school. In general, the purpose of this study was to determine the nutritional status and learning achievement of children at SDN 6 Sanur. This type of research was observational with a cross sectional design. This research was conducted at SDN 6 Sanur in February to April 2019. The results showed that normal nutritional status was 45 (61.64%). Learning achievement can be interpreted as the level of success of students in learning subject matter in schools which are expressed in scores obtained from the results of tests on a number of certain subject matter (Sutanto, 2013). Specific subject matter is namely Religion of Character, PPKN, Indonesian Language, Mathematics, Science, Social Sciences, SBdP, PJOK, Balinese Language, and Language. Most of the samples that had good nutritional status with good learning achievement were 49 (67.12%), but there were still less than 5 (6.85%). Samples with normal nutritional status who have good learning achievement as many as 31 (42.46%), but there are those who are thin (8.22%), obese (9.59%), and obese (5.48%) have learning achievements with good category. Although the sample has a nutritional status that is lacking (very thin and thin) or has more nutritional status (fat and obese) can also have good learning achievements. This happens probably because of how to learn samples both at school and while studying in their homes under the guidance of parents. From this data samples with good nutritional status tend to have good learning achievements. This is probably due to the sample with good nutritional status that will have good concentration when attending school. Besides that the presence of samples in the school will be more optimal.  Keywords: Nutritional Status; Learning achievement; Primary school children